Past, Current and Future Trends of Salicylic Acid and its Derivatives: A Bibliometric Review of Papers from The Scopus Database Published from 2000 to 2021 - Ruzmetov, Abrorbek; Ibragimov, Aziz (Bumi Publikasi Nusantara, 2023)
Theoretical and practical interest in salicylic acid and its derivatives has increased over the last two decades, and with it, academic study in the field has been burgeoning. Most scientometric studies have only focused on a specific property of the topic compounds. None, however, are discussed in the origination progress and prospects of SA and its derivatives. The present study makes a bibliometric review of 2010 papers published during 2000-2021 which were indexed by Scopus in the sub-discipline of salicylic and salicylates. Periodic trends in publishing, as well as prominent research sub-fields, are detected, as are citation patterns, published journal areas of focus, major research institutions, funding organizations, significant research personalities, and the extent to which they interact with one another in research networks. Used keywords indicated the exact publication timeline. Before 2010, the majority of research focused on the synthesis, structure, chemical, and physical properties of salicylic acid and its derivatives. In the past decade, scientists have dedicated significant attention to identifying the bio-properties of the investigated substances.